أعلام الاباضية بإقليم وادي ريغ خلال الفترة الوسيطة - السعيد, بوبكر محمد (Psychology and Education Journal, 2024)
The Wadi Rig region experienced in the intermediate period, especially during the 5th and 6th centuries of the Hijrah, the influx of many sheikhs of the Ibadi sect, so that this period can be considered one of the prosperous periods in the history of the region, especially after the coming of Sheikh Abu Abdullah Muhammad bin Bakr Nu and his choice of the Tin Isli palace (the city of Omar) to reside in the year 409 AH, as this year was called the year of the Ennead, and for this reason I decided to count the scholars who settled in the region, or who were among the inhabitants of the region, or who passed through it, but I was content with the study with only 45 scholars, and I also tried to trace the most important palaces and the tribes that. were mentioned in the sources, and I concluded that some of them still bear the same name, and others whose location is unknown.
Keywords: Ibadisme -- Oued Righ

الإباضية بقصور منطقة وادي ريغ ونشاة نظام العزابة - بن صغير حضري, يمينة; بوبكر, محمد السعيد (‏كتاب أعمل الملتقى الوطني: نظام العزابة نشأته ودوره الحضاري في بلاد المغرب, 2024)
Keywords: Ibadisme -- Oued Righ